ANALISIS SEKTOR TERTINGGAL KABUPATEN TAPANULI UTARA SEBELUM DAN SESUDAH COVID-19 - Syela Maharani (Jurnal Ekonomi & Bisnis, 2023)
This study aims to analyze the effectiveness degree and efficiency of village funds in economic development in Seteluk Atas village, West Sumbawa District in 2016-2021. The type of study used in this study was descriptive quantitative. The types of data used were quantitative and qualitative data, then the source of data in this study was secondary data. The data analysis technique used in this study was quantitative descriptive approach, namely by analyzing target data, expenditure realization and revenue using efficiency and effectiveness ratios. The results of the study showed that the effectiveness of using village funds in economic development in Seteluk Village, West Sumbawa Regency in 2016-2021 is in the less effective category. The village government has not been optimal in using village funds to realize rural economic development using village funds so that the development activities that have been carried out have not reached the set targets. The efficiency of using village funds in economic development in Seteluk Village, West Sumbawa Regency in 2016-2021 is in the very effective category. The use of village funds for rural economic development in Seteluk Village has been carried out efficiently, the output in the form of development activities that have been realized is lower than the budget input used to produce them.